PENGEMBANGAN VIDEO EDUKASI BERBAHASA SUNDA MENGENAI DIET JUMLAH, JENIS, DAN JADWAL (3J) PADA PASIEN DIABETES MELITUS - Siti Nurul Hera; Tati Ruhmawati (Politeknik Kesehatan Kemenkes Bandung, 2025)
Background: Diabetes mellitus is a non-communicable disease with increasing prevalence, with 1,316 cases recorded at the Cicalengka DTP Health Center out of 59,205 in Bandung Regency. Initial studies revealed patients’ limited understanding of the 3J diet (Quantity, Type, Schedule), indicating the need for engaging and culturally appropriate educational media, such as using the Sundanese language. This study aimed to develop and evaluate the feasibility and effectiveness of Sundanese-language educational videos on the 3J diet. Method: This study applied the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) and was conducted at the Cicalengka DTP Health Center from March to June 2025. The population comprised 1,316 diabetes patients, with 42 selected through incidental sampling. Effectiveness was tested using a one-group pretest–posttest design without control. Instruments included interview guides and questionnaires with qualitative and quantitative approaches. Results: The analysis confirmed the need for Sundanese-language video education. The design phase produced materials and storyboards aligned with patient needs. Development yielded highly feasible media with validation scores of 98.8% (content), 80% (language), 100% (media), and 100% (small group). Implementation involved a pretest, media exposure, and posttest with 42 participants. Evaluation showed feedback was actionable. The Wilcoxon test revealed a significant improvement in knowledge of the 3J diet (p = 0.001 < 0.05). Conclusion: The Sundanese-language 3J diet educational video was feasible, culturally relevant, and effective in enhancing diabetes patients’ knowledge at the Cicalengka DTP Health Center.